1999
DOI: 10.1046/j.1365-2672.1999.00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of plasmids that encode streptomycin‐resistance in bacterial epiphytes of apple

Abstract: T .-C. H UA NG A ND T. J . B UR R . 1999. Streptomycin resistance in strains of Pseudomonas syringae pv. papulans, Pantoea agglomerans and a yellow-pigmented, nonfluorescent Pseudomonas sp. (Py), isolated from apple orchards in New York and Washington states, is predominantly associated with strA-strB genes carried on conjugal plasmids (R plasmids). None of 128 resistant Erwinia amylovora strains from the eastern and western USA hybridized with a strA-strB probe, SMP3. Resistant Py strains transfered R plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Considering that cell density plays an important role in conjugation frequency (Normander et al 1998), the concern for build-up of Cu R and Sm R bacterial communities in the phyllosphere is that it increases the likelihood for transfer of resistance genes through horizontal transfer from epiphytic bacteria to Xcc. Huang and Burr (1999) have reported that common fluorescent epiphytic bacteria present in apple orchards, not associated with blister spot of apple, were found to transfer streptomycin resistance efficiently to the pathogen in the laboratory, suggesting that these bacteria may provide a reservoir for streptomycin resistance. Furthermore, Cooksey et al (1990) demonstrated that Cu R saprophytic Pseudomonas putida from a commercial tomato seed lot harbored plasmid-borne resistance genes homologous to those in Pseudomonas syringae pv.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Considering that cell density plays an important role in conjugation frequency (Normander et al 1998), the concern for build-up of Cu R and Sm R bacterial communities in the phyllosphere is that it increases the likelihood for transfer of resistance genes through horizontal transfer from epiphytic bacteria to Xcc. Huang and Burr (1999) have reported that common fluorescent epiphytic bacteria present in apple orchards, not associated with blister spot of apple, were found to transfer streptomycin resistance efficiently to the pathogen in the laboratory, suggesting that these bacteria may provide a reservoir for streptomycin resistance. Furthermore, Cooksey et al (1990) demonstrated that Cu R saprophytic Pseudomonas putida from a commercial tomato seed lot harbored plasmid-borne resistance genes homologous to those in Pseudomonas syringae pv.…”
Section: Discussionmentioning
confidence: 97%
“…This was probably due to the increase of the frequency of Cu R bacteria throughout the orchard due to the copper sprays in previous years. Copper and streptomycin resistant bacteria are naturally present in the environment (Huang and Burr 1999;Norelli et al 1991;van Overbeek et al 2002;Yang et al 1993) and the increased frequency is likely to reflect changes in community structure, adaptation of the initial community as well as selection of resistant populations initially present. Previous studies reported a relationship between exposure to bactericides and the frequency of resistant strains to these chemicals in the environment (Berg et al 2005;Smit et al 1997).…”
Section: Discussionmentioning
confidence: 97%
“…Also working with pepper plants, Canteros et al (1995) showed the exchange of different size plasmids in Xav as early as 4 weeks after donor and recipient strains were separately inoculated into opposite leaves. In Erwinia amylovora, causal agent of fire blight on pear and apple, mobilizable streptomycin resistance genes have been previously identified in common epiphytic bacteria found in orchards (Huang and Burr 1999;Norelli et al 1991). The common plasmid-borne streptomycin resistance genes strA-strB genes have been well characterized in populations of epiphytic bacteria that coexist in close proximity to E. amylovora (Huang and Burr 1999).…”
Section: Discussionmentioning
confidence: 97%
“…For the past 10 years or so, growing numbers of plasmids whose putative Rep proteins are related to the ColE2-P9 Rep protein have been described (Fig. 6 and 7) (1, 2, 3,5,6,9,11,12,13,14,16,19,20,22,25,27,29,31,32,33,36,37,38,39,40,41,44,45,46,49,52,57,61,62). For the ColE2-related plasmids, such as plasmids ColE2-P9, ColE3-CA38, ColE5-099, and ColE2-CA42, the origin sequences where the Rep proteins bind in a plasmid-specific manner and initiate plasmid replication have been identified (19,23,53,60).…”
Section: Resultsmentioning
confidence: 99%
“…c denotes the complementary strand of the database sequence. The (putative) origin sequences of the following plasmids have been presented previously: ColE2-P9, ColE3-CA38, ColE5-099, and ColE2-CA42 (19); pAsa1, pAsa3, and pAsal1 (5); pP (16); pEI2 (13), pUb6060 (3); pMGD2 (61); pT3.2I (2); pJD1 (11,29,32); 86-028NP (38); pDC3000A and pDC3000B (6); pAV505 and pPT23A (14); pPSR1 (46); pFKN (39); CMCP6 chr2 (27); pTiK12 (12); pCPP519 (22); pPSRB101 (49); pPSS4918, pB86-17A, pOK1A, pCG131, pPG2708, pPA0893A, pPSM9032A, pPSM9032B, pPS0693A, pPS0485A, pPS0485B, pPS0485C, pPSTA0893A, and pPSM8810 (62); pPMA4326A and pPMA4326B (44); pTT8 (52); pXAC33 and pXAC64 (9); and pHE1 (57). The asterisks denote the putative origin sequences proposed in this study.…”
Section: Resultsmentioning
confidence: 99%